Silica crystallinity: Characteristics and controlling factors in marine shale of the upper Yangtze area, China. (September 2022) - Liu, Guoheng; Liu, Bo; Liu, Keyu; Zhai, Gangyi; Guo, Zongguang
Abstract: The quartz crystallinity index (QCI) was applied to quantitatively characterise the crystallinity features of silica within the marine shale of the upper Yangtze area. A total of 67 samples, including 63 shale samples, 3 quartz vein samples, and 1 artificial quartz sample as reference, were applied in QCI calculation by X-ray diffraction (XRD). Furthermore, based on the identification and classification of graptolite biozones, a series of experimental analyses, including the total organic carbon (TOC) content, bitumen reflectance, and elemental composition, were conducted to determine the silica origin and controlling factors of crystallinity. The results indicated that biogenic silica in marine shale intervals had an obviously lower crystallinity than silica of other origins. The quartz vein in shale intervals presented the highest silica crystallinity. Silica that experienced a low diagenesis intensity exhibited the lowest crystallinity. Furthermore, biogenic silica in a state of overpressure had a much lower crystallinity than that under normal pressure. The crystallinity of silica in marine shale of the upper Yangtze area is affected by origin, diagenesis intensity, and overpressure. From the perspective of QCI, the Chengkou area is probably the next favourable area for shale gas exploration and development. Highlights: Biogenic silica in marine shale shows lower crystallinity than the silica of other origins. Biogenic silica in high-yielding wells exhibited lower crystallinity than that in low-yielding wells and outcrops. Silica origin, burial depth and constant overpressure are the main factors influencing the silica crystallinity.